Conventional and Transgenic Soybeans: Physiological and Nutritional Differences in Productivity under Sulfur Fertilization - Petineli, Rafael; Moraes, Larissa A. C.; Heinrichs, Reges [UNESP]; Moretti, Luiz Gustavo [UNESP]; Moreira, Adonis (Taylor & Francis Inc, 2020)
Increasingly intensive cropping systems and the introduction of new genetically modified cultivars can lead to a distinct demand for nutrients in soybean crops. This study aims to evaluate the response of two soybean cultivars [with and without tolerance to glyphosate (RR)] to sulfur (S) rates. The experimental design was completely randomized in a 6 x 2 factorial arrangement with four replicates. The treatments consisted of six S rates (0, 10, 20, 40, 80, and 120 mg kg(-1)) and two soybean cultivars from the same breeding program (BRS 317 and BRS 360RR). The increase in S rates resulted in the herbicide sensitive cultivar (BRS 317) having the best physiological indexes (water use efficiency and chlorophyll content) when compared with those of herbicide tolerant cultivar (BRS 360RR), and an increased grain yield (GY), shoot dry weight yield (SDWY), calcium (Ca), boron (B), NO2-N, and iron (Fe) concentration in the leaf tissues. This indicates that the RR gene can cause significant differences in S uptake responses.
Keywords: Glycine max; mineral nutrition; grain yield; yield components